Intense nonclassical light: controllable two-photon Talbot effect - Ooi, Chong Heng Raymond; Lan, B.L. (American Physical Society, 2010)
We study the spatial interference pattern of two-photon correlation function for a coherently phased linear array of N emitters with a double-Raman scheme, each producing nonclassically correlated photon pairs. The N(2) dependence in the two-photon correlation serves as a coherent amplification method for producing intense nonclassical light. The spatial distribution of the correlation can be controlled by lasers, and depends on the detection configuration. For two coincident detectors, the nonclassical correlation displays the spatial Talbot pattern, but modulated by quantum interference effect. The image revival distance is found to be twice the usual Talbot length. For symmetrically located detectors (X(1) = -X(2)), the correlation displays a distorted Talbot pattern with intricate features and lack of symmetry.